Exonization of the LTR transposable elements in human genome - Piriyapongsa, Jittima (BioMed Central, 2007)
BACKGROUND: Retrotransposons have been shown to contribute to evolution of both structure and regulation of protein coding genes. It has been postulated that the primary mechanism by which retrotransposons contribute to structural gene evolution is through insertion into an intron or a gene flanking region, and subsequent incorporation into an exon. RESULTS: We found that Long Terminal Repeat (LTR) retrotransposons are associated with 1,057 human genes (5.8%). In 256 cases LTR retrotransposons were observed in protein-coding regions, while 50 distinct protein coding exons in 45 genes were comprised exclusively of LTR RetroTransposon Sequence (LRTS). We go on to reconstruct the evolutionary history of an alternatively spliced exon of the Interleukin 22 receptor, alpha 2 gene (IL22RA2) derived from a sequence of retrotransposon of the Mammalian apparent LTR retrotransposons (MaLR) family. Sequencing and analysis of the homologous regions of genomes of several primates indicate that the LTR retrotransposon was inserted into the IL22RA2 gene at least prior to the divergence of Apes and Old World monkeys from a common ancestor (~25 MYA). We hypothesize that the recruitment of the part of LTR as a novel exon in great ape species occurred prior to the divergence of orangutans and humans from a common ancestor (~14 MYA) as a result of a single mutation in the proto-splice site. CONCLUSION: Our analysis of LRTS exonization events has shown that the patterns of LRTS distribution in human exons support the hypothesis that LRTS played a significant role in human gene evolution by providing cis-regulatory sequences; direct incorporation of LTR sequences into protein coding regions was observed less frequently. Combination of computational and experimental approaches used for tracing the history of the LTR exonization process of IL22RA2 gene presents a promising strategy that could facilitate further studies of transposon initiated gene evolution.